Nonequilibrium Solidification and Microsegregation in Centrifugally Cast High Speed Steel for Rolls - Klančnik, Urška; Košec, Boris; Mrvar, Primož; Medved, Jožef (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
When regarding as-cast microstructures of highly alloyed metals, microsegregation of alloying elements is a common feature resulting from nonequilibrium conditions during solidification. The aim of this work is to predict the occurrence and severity of microsegregation in highly alloyed, centrifugally cast high speed steel used for rolls. The prediction was performed using thermodynamic Scheil-Gulliver modeling with Thermo-Calc software. The modeled predictions were then compared with differential scanning calorimetry, X-ray diffraction, light and electron microscopy with energy dispersive spectroscopy, all performed on an as-cast roll shell. Results show that chromium, molybdenum and vanadium have the highest affinity for microsegregation. Vanadium tends to form negative microsegregations, while molybdenum and chromium form positive microsegregations. Scanning electron microscopy revealed the presence of complex eutectic carbides, confirming the Scheil-Gulliver nonequilibrium solidification path via two main successive eutectic reactions.